Inverse paired-pulse facilitation in neuroplasticity based on interface-boosted charge trapping layered electronics. (November 2020) - Lee, Ko-Chun; Li, Mengjiao; Chang, Yu-Hsiang; Yang, Shih-Hsien; Lin, Che-Yi; Chang, Yuan-Ming; Yang, Feng-Shou; Watanabe, Kenji; Taniguchi, Takashi; Ho, Ching-Hwa; Lien, Chen-Hsin; Lin, Shu-Ping; et al.
Abstract: Modern technology allows us to mimic biological functions with artificial devices. The human brain, including numerous neural cells that connect via synapses, enables us to handle complex tasks with ultra-low power consumption, which is one of the most important biological components that eager to emulate. Here, we propose and build a simple indium selenide (InSe)-based photonic synaptic device with unique gate tunable behaviours such as time-varying output current, auto-depression rate, and paired-pulse facilitation (PPF). A new inverse PPF behaviour is observed, characterized by the positive correlations to the time interval, which is opposite of those negative ones in previous studies. To unveil the origin of this new finding, both the substrate-dependent persistent photocurrent examination and low-frequency noise (LFN) measurements are performed to investigate the electric-controlled charge trapping/detrapping processes between the InSe and SiO2 interface. Furthermore, we systematically demonstrate such the specific evolution of the flexible plasticity within a low-operation voltage and a wide range of visible spectra. Interestingly, the inverse PPF can be employed to emulate more detailed characteristics of a biological brain such as the age-related changes of synaptic plasticity in real human brains. Thus, we believed that our findings provide a proof-of-concept for systematically mimicking the brain plasticity and advancing the development of energy-efficient artificial brains. Graphical abstract: Inverse Paired-pulse Facilitation in Neuroplasticity based on Interface-boosted Charge Trapping Layered Electronics, is proposed and built by a simple InSe-based photonic synaptic device. Through electric-controlled charge trapping/detrapping processes at the InSe–SiO2 interface, an inverse paired-pulse facilitation (PPF) features are demonstrated for the first time. More interestingly, such the inverse PPF, which definitely increases the neuroplasticity for low-power consumption, can be employed to emulate more detailed characteristics of a biological brain such as the age-related changes of synaptic plasticity in real human brains. Image 1 Highlights: Electric-controlled interfacial charge trapping processes result in bias-dependent persistent photocurrent in InSe devices. The substrate-dependent charge/discharge effect has further proved its universal for layered materials-based systems. The effective trapping density at InSe–SiO2 interface under various gate bias are quantified by low-frequency noise analysis. A new feature of positive correlations between PPF index and time interval (inverse PPF) is found for the first time.